Emotional Labor: The Role of Emotional Intelligence and Work-Family Conflict (WFC) - Nurhamiza Mumina; Ho, Yew Joe (2019)
The global economy is shifting from a manufacturing-based economy to a service-based economy. The service industry contributed more than 50 percent to Malaysia’s GDP between the years 2010 to 2018 with the greatest expansion rate of 6.8 percent compared to the other sectors in 2018. However, the nature of the service industry requires employees to alter their attributes, emotions, and personal responsibilities to cater the professional obligations and organizational demands. Any decision that involves the modification of personal attributes can trigger intra-conflict, which will take a toll on the emotional well-being and distressing work family interaction. Therefore, the ultimate goal of this study is to address the inadequacy of available evidence-based studies on work-family conflict among employees of service industry in Malaysia. A better understanding of the influence of emotional intelligence on work-family conflict is necessary to successfully explain multiple aspects of work-family interface in Malaysia. Subjects were chosen from the service industry in particular, to create a sample that is representative of over half of the workforce in Malaysia. The findings of this study indicate the significant role of the ability to perceive and manage one’s own or others emotion in reducing work family conflict experience. However, the ability to utilize emotions has no significant influence on work-family conflict. Thus, the study suggests organization to equip employees with better emotional skills to reduce emotional labor and work-family conflict.